Globalization and non-traditional security in South Asia - Khan, Abdur Rob.; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (Dhaka : Academic Press and Publisher for Regional Centre for Strategic Studies, Colombo, 2001)
Contributed articles.
Globalization, state, and political process in South Asia / Imtiaz Ahmed -- Globalization, ethnicity, and identity politics : possibilities in South Asia / Jayadeva Uyangoda -- Globalization, growth, and equity : the cases of India and Nepal / Shyamal Krishna Shrestha -- Globalization and human development : the cases of Pakistan and India / Jennifer Bennett -- Information flow, society, and culture : the case of Bhutan / Sonam Kinga, Phuntsho Rapten, and Karma Galay -- Globalization, security technology, and conflicts in South Asia / Santishree D.N.B. Pandit.
Includes bibliographical references and index.
Keywords: South Asia -- Foreign economic relations; South Asia -- Economic conditions; South Asia -- Social conditions